Dakwah Sebagai Ujung Tombak Penanganan Radikalisme Agama di Indonesia - Said, Muhammad (Tasamuh: Jurnal Studi Islam, 2018)
Radicalism in Islam gives depict about the existing of group that exclusive and militant. The attitude without compromise, not respect other people who different faith and crude are “the truth” that they chose. They do not care the destructive reason of their action. Moreover, they do the crude by the naming of religion whereas they are not well confessor of religion. Look at this problem, the writer feels to obligate to reflect back, why Islam is the religion “rahmatan lil ‘alamin”, the religion that loved the peace is becoming the object of all the disturbance action in radical sight. There are two factors of arisen Radical Islam in Indonesia. The first internal factor occurs because the existing of diversion the religion norms. Secondly, external factor for the Muslim whether is occurred by controller or hegemony from western does not support toward applying of Islamic law in the life. The obligation of the rule and public organization of preaching in Indonesia for together handles the radicalism problem of religion so that the goal of preaching to share the conciliation messages, Islam as the welfare religion and the mercy can realize for all the people.